Математичне моделювання гідравлічних режимів водного потоку низьконапірних ГЕС з використанням рівнянь Сен-Венана - Рябенко, Олександр; Попруга, Павло; Поплавський, Дмитро (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
У роботі розглянуто використання диференціального рівняння Сен-Венана при розрахунку гідравлічних режимів водного потоку низьконапірних ГЕС. Наведено математичну модель, що базується на інтегруванні рівнянь Сен-Венана по явній кінцево-різницевій схемі з урахуванням умови стійкості по Куранту. Показано результати розрахунку гідравлічних режимів верхнього б’єфу Нижньодніпровської ГЕС. The paper considers the use of the Saint-Venant differential equation in the calculation of hydraulic modes of water flow of low-pressure hydroelectric power plants. A mathematical model based on the integration of the Saint-Venant equations by an explicit finite-difference scheme, taking into account the Courant stability condition, is presented. The results of the calculation of the hydraulic regimes of the upper basin of Nizhnyodniprovska HPP are shown.